Strategi Mengatasi Resistensi terhadap Perubahan Pendidikan Islam Transformatif di SMPS Islam Sunan Gunung Jati Tulungagung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to find out the strategy to overcome resistance of transformative Islamic educational change which included the aspects of formulation, implementation, and evaluation. This study used a qualitative approach with a field research type at SMPS Islam Sunan Gunung Jati Tulungagung. The data collection techniques used in this study were in-depth interviews, participant observation, and documentation. The data analysis technique in this study was done in three stages, that were data condensation, data presentation, and verification of findings. The results of this study showed that: (1) The formulation strategy to overcome resistance to transformative Islamic educational change begins with building effective communication between the principal teachers and education personnel. (2) The implementation strategy to overcome resistance to transformative Islamic educational change is carried out by implementing inclusive leadership because it plays a very important role in managing resistance and encouraging the adoption of change. (3) The evaluation strategy to overcome resistance to transformative Islamic educational change is carried out by identifying the source of the conflict and resolving it using techniques such as mediation, negotiation, or collaboration.